Implikasi Pedagogis Tentang Tujuan Pendidikan Dalam Qur’an Surat Al-Dzariyat Ayat 56 Dan Al-Baqarah Ayat 30 Kajian Ilmu Pendidikan Islam - Raito, Raito; Rofi, Muhamad Nur (STAI Al-Musaddadiyah Garut, 2023)
The Qur'an, revealed by Allah SWT, serves as a testament to the truth of the Prophet Muhammad SAW, with its primary function being a guide for humanity. The Qur'an addresses various aspects of education and its critical importance in human life. The objectives of education are central and crucial issues in any educational discourse. Numerous verses in the Qur'an encapsulate the purpose of Islamic education, including Surah Al-Dhariyat (51:56) and Surah Al-Baqarah (2:30). These verses implicitly outline educational goals and, more specifically, the objectives of Islamic education. This study aims to describe the pedagogical implications of the educational objectives found in Qur'anic verses Al-Dhariyat 51:56 and Al-Baqarah 2:30 from the perspective of Islamic education studies. The research adopts a library research approach, employing qualitative methods. Based on the findings, it can be concluded that the educational objectives encapsulated in Qur'anic verses Al-Dhariyat 51:56 and Al-Baqarah 2:30 highlight that the ultimate purpose for which Allah created humans is to worship Him and to serve as leaders on Earth. Human existence is not a matter of chance or futility; rather, humans are created with specific purposes and responsibilities. The primary objective of human creation is to serve and worship Allah SWT. This responsibility includes acts of worship and the role of humans as Allah's representatives or stewards (khalifah) on Earth. Keywords: Pedagogical Implications, Educational Objectives, Khalifah